REVIRAL: roadmap for the elimination of viral hepatitis in Latin America - Crespo, Javier; Cabezas, Joaquín; Castro-Narro, Graciela; Cheinquer, Hugo; Contreras, Fernando; Hernandez, Nelia; Perelló, Christie; Ridruejo, Ezequiel; Calleja, José Luís (Frontiers in Public Health, 2025)
The REVIRAL project proposes a comprehensive and tailored strategy for the elimination of viral hepatitis in Latin America, drawing inspiration from successful models in other countries. Despite global advances, the region faces specific barriers, including the lack of universal screening programs, disparities in access to direct-acting antiviral treatments, the presence of fragmented health systems, and the social stigma associated with these infections. These factors hinder progress towards elimination, necessitating collaborative responses tailored to the epidemiological and socioeconomic realities of each country. The project’s structure is organized into three fundamental phases: The first phase involves an initial assessment, where the epidemiological situation of each country will be analyzed, specifically the prevalence and incidence data of viral hepatitis and the response capacity of each country’s health systems. This phase will also identify specific barriers, allowing interventions to be adjusted to local needs. The second phase will focus on the implementation of intervention programs, promoting universal screening, strengthening healthcare personnel training, and implementing health models that enhance linkage-to-care. The third phase will concentrate on monitoring and evaluating results through a global elimination marker, designed to measure and compare progress across countries. The success of REVIRAL will largely depend on the commitment of local governments and international cooperation. If implemented correctly, the project could transform the public health response to viral hepatitis in Latin America and serve as a replicable model for other regions with similar challenges advancing toward the WHO’s global elimination goals set for 2030.